The Effect of Surgical Fear Levels on Postoperative Anxiety and Mobilization Status of Patients Undergoing Laparoscopic Cholecystectomy. - Turhan, Zeynep; Ak, Ezgi Seyhan (Indian Journal of Surgery, 2025)
The aim of this study is to examine the effect of preoperative surgical fear levels on postoperative anxiety and mobilization status in patients undergoing laparoscopic cholecystectomy. The population of the descriptive study consisted of patients who would undergo laparoscopic cholecystectomy in the surgical department of a training and research hospital between August 2023 and February 2024, and the study sample consisted of 125 patients. The İntroductory İnformation Form, the Surgical Fear Scale, the Beck Anxiety Scale, and the Patient Mobility Scale were used to collect data. Ethics committee and institutional approval were obtained prior to the study. The findings obtained in the study were analyzed using the Statistical Package for the Social Sciences (SPSS) Version 26 program (IBM Corp., Armonk, NY, USA). It was found that the mean score of the patients who participated in the study was 19.9 ± 17.85 on the Surgical Fear Scale and their short-term anxiety scores on the subscale of the Surgical Fear Scale were higher than their long-term anxiety scores. The mean score of the Beck Anxiety Scale was 7.08 ± 8.04; the mean total Patient Mobility Score was found to be 71.86 ± 18.33. It was found that age and gender influenced the anxiety level of the patients. There is a statistically significant positive correlation between patients' anxiety before surgery and the anxiety, pain, and difficulty they experience during mobilization. Based on this finding, it was found that as patients' anxiety before surgery increases, their anxiety level and the pain and difficulty they experience during mobilization also increase. It was found that as patients' anxiety increased, so did the pain and difficulty they experienced during mobilization.